(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the theoretical foundations of 4C competencies (critical thinking, creativity, communication, and collaboration) in mother tongue education. Within the framework of the modern educational paradigm, the essence of the competency-based approach is revealed, and the didactic opportunities for developing 4C competencies in the process of teaching the mother tongue are highlighted. Furthermore, the study provides a scientific justification for the use of interactive methods, innovative pedagogical technologies, and effective ways of organizing learning activities aimed at developing these competencies. The article systematically examines the role of 4C competencies in enhancing students’ linguistic, cognitive, and social development, as well as their significance in mother tongue education.